Program "Experiences of Emotional Education in School" for the reduction of anxiety in children of Paraguay (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
Objectives: We aimed to know the effects of the Emotional Education Experiences in School program on the level of anxiety in children. This program was prepared by the authors, based on Cognitive Behavioral Outlines. Methodology: The study began with 104 children from 10 to 12 years old from a school in Yuty, Department of Caazapá, Paraguay, to whom an instrument was applied, SCARED (Screen for Child Anxiety Related Disorders). Validation of the instrument for that population was performed and the sample was selected for convenience after the pre-test. From this selection, a sample of 16 children was established considering the highest scores in the test. Two groups were established (8 experimental group and 8 active control group) with an experimental design pre-test, post test  with active control group. The "Experiences of emotional education in the school" program was applied to the experimental group and the training group applied an emotional education training without work components for anxiety. Results: The intervention in emotional education reduced anxiety at a marginally significant level compared to the control group with average results (r = .42). Conclusions: The results of this study suggest that there is some evidence that training in emotional education in school reduces the level of anxiety in children, estimating that in larger samples, the differences between the groups may be statistically more significant.Keywords: Childhood Anxiety, Intervention, Emotional Education.